Fulfillment Of Regulatory Impact Assessment Principles In Developing Post Of Job Creation Act - Hendra Sukarman; Kana Purwadi; Intan Muttoharoh; Kadar Pamuji (Penerbit USIM, Universiti Sains Islam Malaysia, 2024)
E-Proceedings International Convention on the Basic Structure of Constitution 2021 (ICOBAC 2021) Theme: "Towards Dignifying Islam in the Framework of Rule of Law & Supremacy of Constitution" 15 – 16 December 2021 Organized By: Fakulti Syariah Dan Undang-Undang, Universiti Sains Islam Malaysia (USIM) And Fakulti Pengajian Industri, Universiti Malaysia Pahang (UMP) Collaboration With: Fakulti Syariah Dan Undang-Undang, Universiti Islam Sultan Shariff Ali (UNISSA), Brunei And Fakultas Hukum, Universitas Jendral Soedirman (UNSOED), Indonesia